Efek Bawang Putih (Allium Sativum L) Sebagai Pengobatan Penyakit Jantung Koroner - Olivia Putri Chairunnisa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Coronary heart disease is the leading cause of death in the world. Around 7.4 million people died from coronary heart disease in 2012, which represented 31% of total world deaths and occurred in developing countries with low incomes. Non-pharmacological treatment by maintaining lifestyle such as diet, increasing activity and reducing cigarette consumption (if a smoker). In addition, pharmacological treatment by lowering LDL levels uses statins, bile acid sequestrants, and PCSK-9 inhibitors. However, recently traditional treatments are being developed to reduce the prevalence of atherosclerosis by using garlic or Allium sativum L. Garlic contains more than 100 secondary metabolites that are biologically very useful for the body. Non-volatile amino acids γ glutamyl- Salk (en) il-L-cysteine ​​and essential oils Salk (en) ilsistein sulfoxide or alliin are two of the most important organosulfur compounds in garlic bulbs, that is, and are precursors for most other organosulfur compounds with their levels reached 82% of the total. Garlic has been widely studied in vivo and in vitro. Research that has been developed shows that garlic has pharmacological effects in entity tumorigenesis, antibiosis, inhibition of cancer growth and antianterosclerosis.